Capturing mechanisms of change: Weekly covariation in anger regulation, hostile intent attribution, and children's aggression. Issue 2 (20th January 2022) - Alsem, Sophie C.; Keulen, Janna; Verhulp, Esmée E.; van Dijk, Anouk; De Castro, Bram O.
Abstract: Interventions for children's aggression typically target assumed underlying mechanisms, such as anger regulation and hostile intent attribution. The expectation here is that targeting these mechanisms will result in within‐person changes in aggression. However, evidence for these mechanisms is mostly based on between‐person analyses. We, therefore, examined whether within‐person changes in adaptive anger regulation and hostile intent attribution covaried with within‐person changes in children's aggression. Children ( N  = 223; age 7–12; 46% boys) filled out four weekly report measures to assess adaptive anger regulation, hostile intent attribution, and aggression. The psychometric properties of these novel measures were adequate. Results of multi‐level analyses revealed within‐person effects: weekly changes in adaptive anger regulation and hostile intent attribution covaried with changes in children's aggression. This corresponded with between‐person findings on the same data: children with lower levels of adaptive anger regulation and higher levels of hostile intent attribution reported more aggression than other children. These findings support the idea that targeting anger regulation and hostile intent attribution in interventions may lead to changes in individual children's aggression.